HETEROLOGOUS EXPRESSION OF A CHITINASE GENE FROM AEROMONAS CAVIAEIN PSEUDOMONAS FLUORESCENS - ANTONIUS SUWANTO; AMARILA MALIK; BUDI TJAHJONO; ROB HARLING (BIOTROPIA, 2003)
A transcriptional fusion for an Aeromonas caviae chitinase gene was constructed under the control of a constitutive promoter of the kanaraycin resistance gene (PKmR). The construct was inserted into a medium copy number broad host range plasmid vector to yield recombinant plasmid pAM340, which harbored transcriptional fusion PKmR- chi. Another transcriptional fusion, Ptac-chi, in a recombinant plasmid pAM630, was conducted as comparison. Triparental mating of E. coli  carrying the recombinant plasmids with Pseudomotws fluorescens  5100, a phyllosphere bacterium, was performed. Pseudomonas fluorescens  5100 exconjugants were examined for constitutive expression of chitinase employing a spectrophotometric assay; they showed stronger chitin degradation activity than Escherichia coli transformants. Using a fungal antagonism plate assay, this chitinolytic P. fluorescens, however, could not inhibit selected phytopathogenic fungi. Keywords:    Aeromonas   caviae/  chitinase   gene/transcriptional   fusion/PKm'V   Vtac-chilPseudomonas fluorescens